Best worst movie [videorecording (DVD)] - Stephenson, Michael Paul; Ewing, Darren; Hardy, George; Steadman, Jason; Wright, Jason (New Video Group, 2010)
In 1989, a group of unknown Utah actors starred in what would be crowned the worst movie of all time: Troll 2. Now, after two decades of running from this cinematic disaster, the cast can no longer hide from the legion of followers who celebrate them for their ineptitude.